2022
DOI: 10.1093/jac/dkac049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ceftazidime/avibactam versus best available therapy on mortality from infections caused by carbapenemase-producing Enterobacterales (CAVICOR study)

Abstract: Background Infections caused by carbapenemase-producing Enterobacterales (CPE) are not well represented in pivotal trials with ceftazidime/avibactam. The best strategy for the treatment of these infections is unknown. Methods We conducted a multicentre retrospective observational study of patients who received ≥48 h of ceftazidime/avibactam or best available therapy (BAT) for documented CPE infections. The primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…Despite these two meaningful outcomes, patients treated with CZA did not have a statistically significant difference in hospital mortality from those treated with colistin, 35% vs. 44%; P = 0.156, although there was a numerically decreased mortality that seems clinically significant [7 ▪ ]. Similarly, the CAVICOR study examining CZA vs. best available therapy (mostly gentamicin, tigecycline, fosfomycin, and colistin) for CRE with KPC or OXA-48 in 14 Spanish tertiary centers showed a decrease in 30-day mortality in CZA patients [8 ▪ ]. Interestingly, two unrelated retrospective studies of outcomes of CZA usage in MDRO Gram-negative infections showed a significant difference in mortality in multivariate analysis if the site of infection on initiation of therapy was the lower respiratory tract or the patient was mechanically ventilated [9,10].…”
Section: Ceftazidime-avibactammentioning
confidence: 90%
“…Despite these two meaningful outcomes, patients treated with CZA did not have a statistically significant difference in hospital mortality from those treated with colistin, 35% vs. 44%; P = 0.156, although there was a numerically decreased mortality that seems clinically significant [7 ▪ ]. Similarly, the CAVICOR study examining CZA vs. best available therapy (mostly gentamicin, tigecycline, fosfomycin, and colistin) for CRE with KPC or OXA-48 in 14 Spanish tertiary centers showed a decrease in 30-day mortality in CZA patients [8 ▪ ]. Interestingly, two unrelated retrospective studies of outcomes of CZA usage in MDRO Gram-negative infections showed a significant difference in mortality in multivariate analysis if the site of infection on initiation of therapy was the lower respiratory tract or the patient was mechanically ventilated [9,10].…”
Section: Ceftazidime-avibactammentioning
confidence: 90%
“…More recently the CAVICOR trial [ 44 ], which is a retrospective multicenter study including 349 patients treated for carbapenemase-resistant Enterobacterales -related infection, compared CZA with the best available treatment (amikacin, tobramycin, tigecycline, fosfomycin, and colistin in mono- or combination therapy) and showed lower 30-day mortality and higher clinical or microbiological cure in the CZA treatment arm.…”
Section: What Is To Be Learnt From the Published Studies?mentioning
confidence: 99%
“…In this specific population, studies have shown that the earlier CZA [ 44 ] and CTZ [ 44 , 69 ] are initiated, the more survivors there are. Some studies have also shown that the last resort use of these antibiotics could lead to a loss of opportunity [ 44 , 69 ]. Nevertheless, these studies have led to the documentation of bacteria and antibiotic susceptibility.…”
Section: For Which Patient To Prescribe These New Antibiotics As Empi...mentioning
confidence: 99%
“…In the chapters to follow, the novel β-lactamase inhibitors combination currently in the market (i.e., ceftazidime/avibactam, meropenem-vaborbactam, imipenem-cilastatin-relebactam) and the forthcoming aztreonam-avibactam are presented and discussed, focusing mainly on clinical issues dealing with DTR pathogens in critically ill patients and ICU patients, illustrated in Table 1 . Mechanism of action, spectrum of activity, mechanism of resistance, approved indications, and information on DTR and PDR Gram-negative pathogens are depicted in Table 1 [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ,…”
Section: Carbapenem-resistant Klebsiella Pneumoniaementioning
confidence: 99%
“…The real-world efficacy of ceftazidime-avibactam in the treatment of KPC (+) mostly K. pneumoniae strains was shown in clinical post-marketing studies, proving that in general, when compared to the conventionally prescribed antibiotics, not only higher cure rates were observed, but also lower mortality rates [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. A multicenter prospective observational study with 147 patients (140 with KPC-producing K. pneumoniae (KPC-Kp) and seven with OXA-48 K. pneumoniae isolates with a median MIC to ceftazidime-avibactam of 1 mg/L) was conducted between January 2018 and March 2019 in 14 tertiary hospitals located all over Greece.…”
Section: Carbapenem-resistant Klebsiella Pneumoniaementioning
confidence: 99%